Microwave-assisted synthesis and characterization of microstar shaped zinc oxide - Palomar Pérez, Flor Esthela; Yacamán, Miguel José; Gómez de la Fuente, María Idalia del Consuelo (2012)
A microwave-assisted solution-phase approach has been applied for the synthesis of zinc oxide microstructures. The synthesis procedure was carried out byusing tbe reagents: Zinc nitrate and Methenamine, at stoichiometric ratio. AnaIysis by means ofX-ray Diffraction (XRD) shows a crystalline phase in hexagonal wurtzite arrangement for ZnO. The presence ofmicrostar shaped zinc oxide (2-3Jlm) with nanorods-{5Onm) arranged has been confirmed from High Resolution Scanning Electron Microscopy (HRSEM). The formation ofnanorods was confirmed by Transmission Electron Microscopy. In Raman spectros copy a red shift was detected in the microstructures compared with Zno bulk. High crystalline materials witbout additional post-syn.thesis treatment were found.